Optimalisasi Penggunaan Media Sosial sebagai Media Promosi Kampung Wisata Barokah di Desa Gerdu Kabupaten Karanganyar - Nur Amalina, Husna; Islamiyah, Hanifah; Maditra Permana, Adimas; Adi Wibowo, Ahimsa; Suranto, Joko; Herwindya Baskara Wijaya, Sri; Hans Setyawan Wibowo, Henricus; Primasari, Ina; Tommy Chandra Wijaya, Deniawan (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This study aims to improve the understanding and skills of Kampung Wisata Barokah social media managers in utilizing social media as an effective promotional tool. Social media has proven to be an efficient platform for reaching a wider audience at low cost, especially in the tourism sector. Although Kampung Wisata Barokah has great potential, its social media management is still suboptimal due to the limited knowledge and skills of its managers. Through a participatory approach, the community service team conducted a workshop consisting of three stages: preparation, implementation, and reflection. The training covered creative content creation, understanding social media platform features, and digital marketing strategies. Evaluation results using pre-tests and post-tests showed a significant increase in participants' understanding, from an average of 40% to 100% after the training. The workshop not only provided theoretical knowledge but also practical skills that could be directly applied in promoting tourist destinations. It is hoped that the social media managers of Kampung Wisata Barokah can utilize social media optimally to increase tourist visits and empower the local economy.